Preparation method for preparing cobalt-doped manganese dioxide material by using Co3 [Co (CN) 6] 2 as hard template and application of cobalt-doped manganese dioxide material

Co3[Co(CN)6]2 Prussian blue nanocubes were used as templates to prepare cobalt-doped manganese dioxide materials, which solved the structural stability of manganese dioxide materials during zinc ion embedding/de-embedding process and The problem of zinc ion diffusion has achieved efficient electrochemical performance improvement and adaptability to large-scale production.

CN119390126APending Publication Date: 2025-02-07DALIAN UNIV OF TECH

Patent Information

Application Number
CN202411479325.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing manganese dioxide positive electrode materials are prone to irreversible phase change and volume change during the repeated embedding/de-embedding of zinc ions, resulting in structural collapse and hindered diffusion of zinc ions, reducing the stability of the redox reaction of energy storage batteries.

Method used

Co3[Co(CN)6]2 Prussian blue nanocubes were used as hard templates to prepare cobalt-doped manganese dioxide materials through two-step synthesis method (liquid phase coprecipitation reaction and hydrothermal synthesis), avoiding high-temperature calcination and electricity High energy-consuming steps such as deposition can be synchronized to complete morphological control and cobalt doping optimization.

Benefits of technology

The prepared cobalt-doped manganese dioxide material has excellent electrochemical properties, improves zinc ion diffusion efficiency and material structural stability, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390126A_ABST
    Figure CN119390126A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application for preparing a cobalt-doped manganese dioxide material by taking Co3 [Co (CN) 6] 2 as a hard template, and belongs to the technical field of electrode material preparation. The preparation method comprises the following steps: firstly, preparing a Co3 [Co (CN) 6] 2 type Prussian blue nano cubic material through a liquid phase coprecipitation reaction method; and then preparing the cobalt-doped manganese dioxide material with a loose porous structure by taking the Co3 [Co (CN) 6] 2 type Prussian blue nano cubic material as a hard template and potassium permanganate as a reaction raw material and adopting a hydrothermal synthesis method, specifically, forming a submicron cube with the size of 200-700nm by combining nanosheets with the thickness of about 10-20nm, and preparing the cobalt-doped manganese dioxide material with the loose porous structure by adopting a hydrothermal synthesis method. And an optimization strategy of Co atom doping of manganese dioxide and nanosheet morphology control is synchronously completed. When the material is used as an electrode material, the conductivity of the manganese dioxide electrode material is greatly improved, the capacity of an aqueous zinc ion battery is improved, and the material has excellent charge-discharge cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode material preparation, and relates to a preparation method and application of a cobalt-doped manganese dioxide material using Co3[Co(CN)6]2 as a hard template. Background Art

[0002] In order to cope with the energy crisis and extreme climate, the new energy industry has entered a new period of prosperity. Energy innovations in the fields of transportation and renewable energy applications have jointly promoted the prosperity of the energy storage battery and power battery markets. Since the mechanism of weakly acidic Zn-MnO2 batteries was determined in 2011, aqueous zinc-ion batteries have attracted much attention. Compared with lithium-ion batteries, they have higher power density and can be combined with other energy storage systems to achieve complementarity. They are suitable for application scenarios such as the storage of renewable energy and the power recovery of large electric vehicles, which have high requirements for the power density of energy storage systems. At the same time, aqueous zinc-ion batteries have obvious advantages in safety and cost, and have great potential in the application scenarios of wearable smart devices. The key point of the commercial development of rechargeable aqueous zinc-ion batteries is the excellent performance of positive electrode materials.

[0003] At present, the commonly used positive electrode materials for aqueous zinc-ion batteries are manganese-based materials, vanadium-based materials, Prussian blue materials and transition metal sulfides. Among them, Prussian blue materials belong to metal organic framework materials, which have the advantages of strong structural controllability, large specific surface area and high porosity. Their large enough three-dimensional open framework structure can enhance the zinc ion transmission capacity. However, Prussian blue materials have poor zinc storage capacity and a narrow application range. Manganese-based materials show significant advantages such as high working potential, high energy density and low cost. Manganese dioxide is considered to be the most promising manganese-based material due to its environmental friendliness, high theoretical capacity and rich crystal structure. In the field of alkaline dry batteries, manganese dioxide materials have been fully explored and applied, and zinc-manganese batteries still occupy about 42% of the replaceable battery market share. The determination of the mechanism of weakly acidic Zn-MnO2 batteries has led to a boom in the development of manganese dioxide in aqueous zinc-ion batteries. Problems that need to be solved to further develop the energy storage performance of manganese dioxide: During the repeated insertion / deinsertion of zinc ions, the manganese dioxide positive electrode material will undergo irreversible phase change and volume change. Such problems combined with the manganese dissolution phenomenon can easily lead to the collapse of the manganese dioxide structure. At the same time, the strong electrostatic interaction between zinc ions and manganese dioxide will hinder the diffusion of zinc ions and reduce the redox reaction stability of zinc ion batteries.

[0004] At present, the mainstream optimization methods of manganese dioxide include strategies such as morphology design, defect engineering and composite modification. Among them, the heteroatom doping method can improve the overall conductivity of manganese dioxide, and at the same time use the associated oxygen vacancies near the heteroatoms entering the crystal structure to reduce the electrostatic interaction between zinc ions and manganese dioxide layers. However, this method usually cannot take into account the control of the material morphology, and the uneven heteroatom doping easily leads to the aggregation of oxygen vacancies, which causes the crystal structure to deteriorate and the structural stability of the manganese dioxide material to decrease. Patent CN118084064A uses a chemical coprecipitation method to drop an aqueous solution containing a divalent cobalt salt into a mixed aqueous solution of a divalent manganese salt and a persulfate to prepare cobalt-doped manganese dioxide. However, the morphology uniformity of the manganese dioxide material obtained is poor, and the nano-morphology of manganese dioxide needs to be further controlled to obtain better electrochemical performance. Patent CN117293307A uses an ion infiltration method to place the previously prepared manganese dioxide material into a metal hydrochloride, metal sulfate or metal nitrate solution for 3 to 7 days to complete the heteroatom infiltration. However, the method requires a long soaking time to ensure the gentle penetration of heteroatoms, and inevitably weakens and damages the nanostructure of manganese dioxide. The template method focuses on controlling the morphology and structure of the material, which can increase the effective specific surface area of ​​the material and enhance the structural stability of the material, but most templates require high-temperature calcination preparation or use high-temperature calcination to assist crystallization, which increases the energy consumption and cost required for the method. Patent CN111573714A obtains the template and manganese dioxide composite materials respectively by high-temperature calcination under two different atmospheres, which has high energy consumption and large batch production costs. Patent CN106409522A uses hollow carbon spheres as templates to prepare manganese dioxide composite materials. This method can obtain a manganese dioxide composite material with uniform morphology, but the preparation of the template requires high-temperature calcination at 500-900°C in a nitrogen atmosphere and repeated leaching with hydrofluoric acid, which has a high production cost and a cumbersome process, which is not conducive to large-scale production. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a preparation method and application of a cobalt-doped manganese dioxide material prepared by using Co3[Co(CN)6]2-type Prussian blue nanocube as a hard template. The preparation method is a two-step synthesis method (solution coprecipitation method, hydrothermal synthesis). First, potassium citrate, cobalt chloride hexahydrate and potassium cobalt cyanide are used as raw materials, and a liquid phase coprecipitation reaction method is adopted to prepare Co3[Co(CN)6]2-type Prussian blue nanocube by controlling the amount of potassium citrate and the aging time. Then, Co3[Co(CN)6]2-type Prussian blue nanocube is used as a hard template, potassium permanganate and potassium hydroxide are used as raw materials for manganese dioxide, and a hydrothermal synthesis method is adopted to prepare a cobalt-doped manganese dioxide material. The synthesis process of the present invention does not require high-energy-consuming steps such as high-temperature calcination or electrodeposition, and does not need to perform secondary heteroatom doping on the basis of nanostructure adjustment. The raw material source is abundant and the cost is low, and no expensive surfactant is required, which is suitable for large-scale production.

[0006] The technical solution of the present invention to solve the problem is:

[0007] A method for preparing a cobalt-doped manganese dioxide material using Co3[Co(CN)6]2 as a hard template, wherein the cobalt-doped manganese dioxide is a loose porous submicron cube with a size of 200 to 700 nanometers and composed of nanosheets with a thickness of 10 to 20 nanometers. The cobalt-doped manganese dioxide nanosheets are relatively pure δ-MnO2 (PDF#13-0105).

[0008] The preparation method of the cobalt-doped manganese dioxide material uses Co3[Co(CN)6]2-type Prussian blue nanocubes as hard templates to simultaneously complete two optimization strategies of morphology control and cobalt doping; a two-step synthesis method is adopted, firstly liquid phase coprecipitation reaction is carried out, and then hydrothermal synthesis is carried out, and the specific steps are as follows:

[0009] Step 1, dissolving potassium cobalt cyanide in deionized water to prepare a potassium cobalt cyanide solution;

[0010] The concentration of the potassium cobalt cyanide solution is 0.016-0.048 mol / L;

[0011] Step 2, dissolving potassium citrate and cobalt chloride hexahydrate in deionized water to prepare a mixed solution I, slowly dropping the potassium cobalt cyanide solution into the mixed solution I under vigorous stirring, and continuing stirring for 0.5 to 2 hours;

[0012] In the mixed solution I, the concentration of potassium citrate is 0.024-0.06 mol / L; the concentration of cobalt chloride hexahydrate is 0.04-0.06 mol / L;

[0013] Step 3, the stirred mixture is allowed to stand for aging, the sample is filtered, washed with deionized water for multiple times, and dried at 60-80° C. to obtain Co3[Co(CN)6]2-type Prussian blue nanocubic material;

[0014] The aging time is 20 to 26 hours;

[0015] Step 4, ultrasonically diffusing Co3[Co(CN)6]2-like Prussian blue nanocubes into deionized water to prepare a Co3[Co(CN)6]2 suspension;

[0016] In the Co3[Co(CN)6]2 suspension, the concentration of Co3[Co(CN)6]2 Prussian blue nanocubes is 3-6 g / L;

[0017] Step 5, dissolving potassium hydroxide and potassium permanganate in deionized water to prepare a mixed solution II, adding the Co3[Co(CN)6]2 suspension to the mixed solution II while stirring, and continuing to stir;

[0018] In the mixed solution II, the concentration of potassium hydroxide is 0.15-0.3 mol / L; the concentration of potassium permanganate is 0.04-0.06 mol / L; the volume ratio of Co3[Co(CN)6]2 suspension to the mixed solution II is 3:20-7:20;

[0019] Step 6, transferring the stirred mixture to a reactor for hydrothermal synthesis, filtering the sample, washing it with deionized water for multiple times, and drying it at 60-80° C. to obtain a cobalt-doped manganese dioxide material;

[0020] The temperature of the hydrothermal synthesis is 160-190°C and the time is 8-12h.

[0021] In the above reaction process, if the amount of potassium citrate used is too little or the aging time is too long, the nano-morphology uniformity of Co3[Co(CN)6]2-type Prussian blue will be poor, and the morphology of cobalt-doped manganese dioxide cannot be well controlled. Therefore, the amount of potassium citrate used and the aging time need to be strictly controlled. If the amount of potassium hydroxide used is too little, the micro-morphology of manganese dioxide tends to be nanorods, and the doping efficiency and morphology control effect of Co3[Co(CN)6]2-type Prussian blue nanocubes are reduced. If the amount of potassium hydroxide used is too high, the growth of manganese dioxide will be inhibited, and cobalt-doped manganese dioxide with uniform size cannot be obtained, and the yield of hydrothermal synthesis is reduced. Therefore, the amount of potassium hydroxide used needs to be strictly controlled.

[0022] The cobalt-doped manganese dioxide material prepared by the above method is applied to aqueous zinc ion batteries, as follows:

[0023] Cobalt-doped manganese dioxide material, polytetrafluoroethylene and acetylene black are mixed in a mass ratio of 7:1:2, and an appropriate amount of ethanol is added to fully mix the three to make a slurry, which is rolled into a sheet and cut according to the size requirements of the electrode. Then, it is pressed on a titanium sheet and dried in a drying oven at 60-80°C for 6-10 hours to obtain a positive electrode sheet for an aqueous zinc ion battery.

[0024] Aqueous zinc-ion batteries assembled with cobalt-doped manganese dioxide materials prepared with Co3[Co(CN)6]2-type Prussian blue nanocubes as hard templates exhibit excellent electrochemical performance. For example, when a mixed solution of 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate is used as the electrolyte, the specific capacity is 310-355 mAh / g (working potential window is 0.9-1.8 V) during constant current charge and discharge at a current density of 0.1 A / g.

[0025] Compared with the prior art, the beneficial effects achieved by adopting the technical solution of the present invention are:

[0026] The preparation method of the invention is a two-step synthesis method, firstly, liquid phase coprecipitation reaction is carried out to obtain Co3[Co(CN)6]2 type Prussian blue nanocubes, and then hydrothermal synthesis is carried out to obtain manganese dioxide. The process is simple, and secondary heteroatom doping is not required on the basis of nanostructure adjustment. The preparation method of the invention requires abundant raw material sources and low cost, does not require the use of expensive surfactants, and does not require high-energy-consuming steps such as high-temperature calcination and electrodeposition, and is suitable for large-scale production. The preparation method of the invention uses Co3[Co(CN)6]2 type Prussian blue nanocubes as hard templates, and its structure is composed of the mutual coordination of Co(Ⅱ) and Co(Ⅲ) and cyano (-CN-), and its The special structure ensures the uniformity of cobalt doping and enhances the conductivity of manganese dioxide; the cobalt doping strategy improves the zinc ion diffusion efficiency between manganese dioxide layers and improves the ion transfer capacity of manganese dioxide; the microscopic morphology of the prepared cobalt-doped manganese dioxide is a loose porous submicron cube composed of manganese dioxide nanosheets, which greatly increases the effective reaction area of ​​manganese dioxide and enhances its capacitance. The loose porous structure can effectively buffer the stress caused by phase change in the charge and discharge cycle and improve the structural stability and cycle performance of manganese dioxide; the method simultaneously completes the cobalt doping and nanostructure adjustment of manganese dioxide, avoids the impact of secondary heteroatom doping on the crystal structure of manganese dioxide, and improves the structural integrity of manganese dioxide. Therefore, the cobalt-doped manganese dioxide material prepared by the method of the present invention using Co3[Co(CN)6]2 nanocube as a hard template has important application prospects in the field of aqueous zinc ion battery industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is the XRD pattern of the cobalt-doped manganese dioxide material prepared in Example 1;

[0028] Figure 2 is a SEM image of the Co3[Co(CN)6]2-like Prussian blue nanocube prepared in Example 1;

[0029] Figure 3 is a SEM image of the cobalt-doped manganese dioxide material prepared in Example 1;

[0030] Figure 4 is a TEM image of the cobalt-doped manganese dioxide material prepared in Example 1;

[0031] Figure 5 This is a constant current charge and discharge curve of an aqueous zinc ion battery assembled with a cobalt-doped manganese dioxide material prepared in Example 1 at a current density of 0.1 A / g;

[0032] Figure 6 This is a constant current charge and discharge curve of an aqueous zinc ion battery assembled with a cobalt-doped manganese dioxide material prepared in Example 1 at a current density of 1.5 A / g;

[0033] Figure 7 This is the cyclic voltammetry curve of the aqueous zinc ion battery assembled with the cobalt-doped manganese dioxide material prepared in Example 1 at a scan rate of 1 mV / s.

[0034] Figure 8 is the XRD pattern of the cobalt-doped manganese dioxide material prepared in Example 2;

[0035] Fig. 9 is a SEM image of the Co3[Co(CN)6]2-like Prussian blue nanocube prepared in Example 2;

[0036] Fig.10 is a SEM image of the cobalt-doped manganese dioxide material prepared in Example 2;

[0037] Fig.11 is a TEM image of the cobalt-doped manganese dioxide material prepared in Example 2;

[0038] Fig.12 This is the constant current charge and discharge curve of the aqueous zinc ion battery assembled with the cobalt-doped manganese dioxide material prepared in Example 2 at a current density of 0.1 A / g;

[0039] Fig.13 This is the constant current charge and discharge curve of the aqueous zinc ion battery assembled with the cobalt-doped manganese dioxide material prepared in Example 2 at a current density of 1.5 A / g;

[0040] Fig.14 This is the cyclic voltammetry curve of the aqueous zinc ion battery assembled with the cobalt-doped manganese dioxide material prepared in Example 2 at a scan rate of 1 mV / s.

[0041] Fig.15 is the XRD pattern of the cobalt-doped manganese dioxide material prepared in Example 3;

[0042] Fig.16 is a SEM image of the Co3[Co(CN)6]2-like Prussian blue nanocube prepared in Example 3;

[0043] Fig.17 is a SEM image of the cobalt-doped manganese dioxide material prepared in Example 3;

[0044] Fig.18 is a TEM image of the cobalt-doped manganese dioxide material prepared in Example 3;

[0045] Fig.19 This is the constant current charge and discharge curve of the aqueous zinc ion battery assembled with the cobalt-doped manganese dioxide material prepared in Example 3 at a current density of 0.1 A / g;

[0046] Fig. 20This is the constant current charge and discharge curve of the aqueous zinc ion battery assembled with the cobalt-doped manganese dioxide material prepared in Example 3 at a current density of 1.5 A / g;

[0047] Fig.21 This is the cyclic voltammetry curve of the aqueous zinc ion battery assembled with the cobalt-doped manganese dioxide material prepared in Example 3 at a scan rate of 1 mV / s. DETAILED DESCRIPTION

[0048] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.

[0049] Example 1

[0050] Weigh 0.399g of potassium cobalt cyanide and dissolve it in 25mL of deionized water to prepare a potassium cobalt cyanide solution; weigh 0.357g of cobalt chloride hexahydrate and 0.184g of potassium citrate and dissolve them in 25mL of deionized water to prepare a mixed solution I; under vigorous stirring, slowly drop the potassium cobalt cyanide solution into the mixed solution I and continue stirring for 2 hours; stop stirring and let the mixture stand at room temperature for aging for 20 hours; filter the sample, wash it with deionized water 3 times, and dry it at 60°C to obtain a Co3[Co(CN)6]2 type Prussian blue material; weigh 21mgCo3[Co(CN)6]2 type Prussian blue Prussian blue material, add it to 7mL deionized water, ultrasonicate for 10 minutes, prepare Co3[Co(CN)6]2 type Prussian blue material suspension; weigh 0.19mg potassium permanganate and 0.168mg potassium hydroxide and dissolve them in 20mL deionized water to prepare mixed solution II; under stirring, add Co3[Co(CN)6]2 type Prussian blue material suspension to mixed solution II, continue stirring for 20 minutes, then transfer the sample into a reactor, heat at 190℃ for 8 hours; filter the sample, wash it three times with deionized water, and dry it at 60℃ to obtain cobalt-doped manganese dioxide. Figure 1 The XRD image shows that the sample is relatively pure δ-MnO2, without obvious impurity peaks. Figure 2 It can be seen that the size of Co3[Co(CN)6]2-type Prussian blue materials is 400-600nm, and its size uniformity is good. Figure 3 It can be seen that the microstructure of the cobalt-doped manganese dioxide material is a submicron cube with a size of 500 to 700 nm composed of manganese dioxide nanosheets with a thickness of 10 to 20 nm. Figure 4 The lattice fringes of the doped manganese dioxide material are obvious and the structural stability is better.

[0051] Application example of embodiment 1

[0052] The cobalt-doped manganese dioxide material prepared in Example 1, acetylene black and polytetrafluoroethylene were mixed in a mass ratio of 7:2:1, ethanol was added to make a slurry, and the slurry was rolled into sheets several times. A 20 mg sheet was cut and pressed on a titanium sheet to make an electrode sheet, and then dried in a drying oven at 60°C for 6 hours. The electrochemical performance of the aqueous zinc ion battery was tested, in which the cobalt-doped manganese dioxide was used as the positive electrode, the zinc sheet was used as the negative electrode, and the electrolyte was a mixed solution of 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate. Figure 5 and Figure 6 It can be measured that the specific capacity of the cobalt-doped manganese dioxide material electrode during constant current charge and discharge at a current density of 0.1A / g is 310mAh / g, and the specific capacity during constant current charge and discharge at a current density of 1.5A / g is 110mAh / g (the working potential window is 0.9-1.8V), showing excellent electrochemical performance. Figure 7 It can be measured that the cobalt-doped manganese dioxide material electrode exhibits a clear redox peak in the cyclic voltammetry at a scan rate of 1 mV / s, and a significantly stronger response current appears.

[0053] Example 2

[0054] 0.133 g of potassium cobalt cyanide was dissolved in 25 mL of deionized water to prepare a potassium cobalt cyanide solution; 0.238 g of cobalt chloride hexahydrate and 0.552 g of potassium citrate were dissolved in 25 mL of deionized water to prepare a mixed solution I; under vigorous stirring, the potassium cobalt cyanide solution was slowly dripped into the mixed solution I and stirred for 0.5 hour; stirring was stopped and the mixture was allowed to stand at room temperature for aging for 26 hours; the sample was filtered, washed with deionized water for 3 times, and dried at 70°C to obtain a Co3[Co(CN)6]2 type Prussian blue material; 18 mg of Co3[Co(C N)6]2 type Prussian blue, add it to 3mL deionized water, ultrasonic for 10 minutes, prepare Co3[Co(CN)6]2 suspension; weigh 0.127mg potassium permanganate and 0.337mg potassium hydroxide and dissolve them in 20mL deionized water to prepare mixed solution II; under stirring, add Co3[Co(CN)6]2 suspension to mixed solution II, continue stirring for 20 minutes, then transfer the sample into the reactor, heat at 160℃ for 12 hours; filter the sample, wash it three times with deionized water, and dry it at 70℃ to obtain cobalt-doped manganese dioxide. Figure 8 The XRD image shows that the sample is relatively pure δ-MnO2, without obvious impurity peaks. Fig. 9 It can be seen that the size of Co3[Co(CN)6]2 type Prussian blue material is 200~400nm, and its size uniformity is good. Fig.10 It can be seen that the microstructure of the cobalt-doped manganese dioxide material is composed of manganese dioxide nanosheets with a thickness of 10 to 15 nm and submicron cubes with a size of 200 to 400 nm. Fig.11It can be seen that the lattice fringes of the doped manganese dioxide material are obvious and the structural stability is better.

[0055] Application example of embodiment 2

[0056] The cobalt-doped manganese dioxide material prepared in Example 2, acetylene black and polytetrafluoroethylene were mixed in a mass ratio of 7:2:1, ethanol was added to make a slurry, and the slurry was rolled into sheets several times. A 20 mg sheet was cut and pressed on a titanium sheet to make an electrode sheet, and then dried in a drying oven at 70°C for 8 hours. The electrochemical performance of the aqueous zinc ion battery was tested, in which the cobalt-doped manganese dioxide was used as the positive electrode, the zinc sheet was used as the negative electrode, and the electrolyte was a mixed solution of 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate. Fig.12 and Fig.13 It can be measured that the specific capacity of the cobalt-doped manganese dioxide material electrode during constant current charge and discharge at a current density of 0.1A / g is 330mAh / g, and the specific capacity during constant current charge and discharge at a current density of 1.5A / g is 120mAh / g (the working potential window is 0.9-1.8V), showing excellent electrochemical performance. Fig.14 It can be measured that the cobalt-doped manganese dioxide material electrode exhibits a clear redox peak in the cyclic voltammetry at a scan rate of 1 mV / s, and a significantly stronger response current appears.

[0057] Example 3

[0058] Weigh 0.266g of potassium cobalt cyanide and dissolve it in 25mL of deionized water to prepare a potassium cobalt cyanide solution; weigh 0.286g of cobalt chloride hexahydrate and 0.368g of potassium citrate and dissolve them in 25mL of deionized water to prepare a mixed solution I; under vigorous stirring, slowly drop the potassium cobalt cyanide solution into the mixed solution I and continue stirring for 1 hour; stop stirring and let the mixture stand at room temperature for aging for 24 hours; filter the sample, wash it with deionized water for 3 times, and dry it at 80°C to obtain a Co3[Co(CN)6]2 type Prussian blue material; weigh 20mgCo3[Co(CN )6]2 type Prussian blue, add it to 5mL deionized water, ultrasonic for 10 minutes, prepare Co3[Co(CN)6]2 suspension; weigh 0.158mg potassium permanganate and 0.281mg potassium hydroxide and dissolve them in 20mL deionized water to prepare mixed solution II; under stirring, add Co3[Co(CN)6]2 suspension to mixed solution II, continue stirring for 20 minutes, then transfer the sample into a reactor, heat at 180℃ for 10 hours; filter the sample, wash it three times with deionized water, and dry it at 80℃ to obtain cobalt-doped manganese dioxide. Fig.15 The XRD image shows that the sample is relatively pure δ-MnO2, without obvious impurity peaks. Fig.16 It can be seen that the size of Co3[Co(CN)6]2-type Prussian blue materials is 300-400nm, and its size uniformity is good. Fig.17 It can be seen that the microstructure of the cobalt-doped manganese dioxide material is a submicron cube with a size of 300 to 400 nm composed of manganese dioxide nanosheets with a thickness of 10 to 15 nm. Fig.18 It can be seen that the lattice fringes of the doped manganese dioxide material are obvious and the structural stability is better.

[0059] Application example of embodiment 3

[0060] The cobalt-doped manganese dioxide material prepared in Example 3, acetylene black and polytetrafluoroethylene were mixed in a mass ratio of 7:2:1, ethanol was added to make a slurry, and the slurry was rolled into sheets several times. A 20 mg sheet was cut and pressed on a titanium sheet to make an electrode sheet, and then dried in a drying oven at 80°C for 8 hours. The electrochemical performance of the aqueous zinc ion battery was tested, in which the cobalt-doped manganese dioxide was used as the positive electrode, the zinc sheet was used as the negative electrode, and the electrolyte was a mixed solution of 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate. Fig.19 and Fig. 20 It can be measured that the specific capacity of the cobalt-doped manganese dioxide material electrode during constant current charge and discharge at a current density of 0.1A / g is 355mAh / g, and the specific capacity during constant current charge and discharge at a current density of 1.5A / g is 145mAh / g (the working potential window is 0.9-1.8V), showing excellent electrochemical performance. Fig.21 It can be measured that the cobalt-doped manganese dioxide material electrode exhibits a clear redox peak in the cyclic voltammetry at a scan rate of 1 mV / s, and a significantly stronger response current appears.

Claims

1. A method for preparing a cobalt-doped manganese dioxide material using Co3[Co(CN)6]2 as a hard template, characterized in that: Co3[Co(CN)6]2-type Prussian blue nanocubes were used as hard templates to simultaneously complete the two optimization strategies of morphology control and cobalt doping. A two-step synthesis method was adopted, firstly liquid phase coprecipitation reaction and then hydrothermal synthesis. The specific steps are as follows: Step 1, dissolving potassium cobalt cyanide in deionized water to prepare a potassium cobalt cyanide solution; The concentration of the potassium cobalt cyanide solution is 0.016-0.048 mol / L; Step 2, dissolving potassium citrate and cobalt chloride hexahydrate in deionized water to prepare a mixed solution I, slowly dropping the potassium cobalt cyanide solution into the mixed solution I under vigorous stirring, and continuing stirring for 0.5 to 2 hours; In the mixed solution I, the concentration of potassium citrate is 0.024-0.06 mol / L; the concentration of cobalt chloride hexahydrate is 0.04-0.06 mol / L; Step 3, the stirred mixture is allowed to stand for aging, the sample is filtered, washed with deionized water for multiple times, and dried at 60-80° C. to obtain Co3[Co(CN)6]2-type Prussian blue nanocubic material; Step 4, ultrasonically diffusing Co3[Co(CN)6]2-like Prussian blue nanocubes into deionized water to prepare a Co3[Co(CN)6]2 suspension; In the Co3[Co(CN)6]2 suspension, the concentration of Co3[Co(CN)6]2 Prussian blue nanocubes is 3-6 g / L; Step 5, dissolving potassium hydroxide and potassium permanganate in deionized water to prepare a mixed solution II, adding the Co3[Co(CN)6]2 suspension to the mixed solution II while stirring, and continuing to stir; In the mixed solution II, the concentration of potassium hydroxide is 0.15-0.3 mol / L; the concentration of potassium permanganate is 0.04-0.06 mol / L; the volume ratio of Co3[Co(CN)6]2 suspension to the mixed solution II is 3:20-7:20; Step 6: Transfer the stirred mixture to a reactor for hydrothermal synthesis, filter the sample, wash it with deionized water for multiple times, and dry it at 60-80° C. to obtain a cobalt-doped manganese dioxide material.

2. The method for preparing a cobalt-doped manganese dioxide material using Co3[Co(CN)6]2 as a hard template according to claim 1, characterized in that: In step 3, the aging time is 20 to 26 hours.

3. A method for preparing a cobalt-doped manganese dioxide material using Co3[Co(CN)6]2 as a hard template according to claim 1 or 2, characterized in that: In step 6, the temperature of the hydrothermal synthesis is 160-190° C., and the time is 8-12 hours.

4. The method for preparing a cobalt-doped manganese dioxide material using Co3[Co(CN)6]2 as a hard template according to claim 1 or 2, characterized in that: The cobalt-doped manganese dioxide is a loose porous submicron cube with a size of 200 to 700 nanometers and composed of nanosheets with a thickness of 10 to 20 nanometers.

5. The cobalt-doped manganese dioxide material prepared by the preparation method according to any one of claims 1 to 3 is applied to aqueous zinc ion batteries.

6. The use according to claim 5, characterized in that: The details are as follows: cobalt-doped manganese dioxide material, polytetrafluoroethylene and acetylene black are mixed in a mass ratio of 7:1:2, ethanol is added to fully mix the three, and a slurry is made, which is rolled into a sheet and cut according to the size requirements of the electrode, and then pressed onto a titanium sheet, and dried in a drying oven at 60-80°C for 6-10 hours to obtain an aqueous zinc ion battery positive electrode sheet.

Citation Information

Patent Citations

  • Manganese dioxide-coated hollow carbon spheres and preparation method and application thereof

    CN106409522A

  • Lithium ion battery negative electrode composite material with stannic oxide / manganese dioxide multistage hollow structure and preparation method of lithium ion battery negative electrode composite material

    CN111573714A

  • Metal ion intercalated manganese dioxide as well as preparation method and application thereof

    CN117293307A

  • Ion-doped gamma-MnO2 nano material as well as preparation method and application thereof

    CN118084064A

Cited By

  • Modified layered manganese dioxide cathode active material, its preparation and application in aqueous zinc-ion batteries

    CN120097389B

  • Flexible transparent cobalt-doped manganese dioxide zinc ion battery positive pole piece and preparation method thereof

    CN121726346A

  • Preparation method and application of boron-doped manganese dioxide nano material

    CN122355351A